2018
DOI: 10.1111/jnp.12173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive‐driven activity of daily living impairment in non‐demented Parkinson's patients

Abstract: The core criterion for Parkinson's disease dementia (PDD) is the impairment in activities of daily living (ADL) function primarily caused by cognitive, not motor symptoms. There is evidence to assume that mild ADL impairments in mild cognitive impairment (PD‐MCI) characterize those patients at high risk for dementia. Data of 216 Parkinson's disease (PD) patients assessed with comprehensive motor and neuropsychological assessments were analysed. Based on linear regression models, subscores of the Functional Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 49 publications
5
35
1
Order By: Relevance
“…This further underlines our findings that the performance in the ETAM is dependent on cognitive functions and its tasks require attention, memory, executive, and visuospatial functions. These results are consistent with other studies (Becker et al, 2018;Bronnick et al, 2006;Cahn et al, 1998;Higginson et al, 2013;Maeshima, Itakura, Nakagawa, Nakai, & Komai, 1997;Pirogovsky, Woods, Filoteo, & Gilbert, 2012). Regarding the individual items, only 'tea making' and 'alarm clock' are not related to cognitive dysfunction, further indicating that these items are not cognitively demanding enough to detect early signs of iADL impairment.…”
Section: Reliability and Item-validity Of The Etamsupporting
confidence: 91%
See 2 more Smart Citations
“…This further underlines our findings that the performance in the ETAM is dependent on cognitive functions and its tasks require attention, memory, executive, and visuospatial functions. These results are consistent with other studies (Becker et al, 2018;Bronnick et al, 2006;Cahn et al, 1998;Higginson et al, 2013;Maeshima, Itakura, Nakagawa, Nakai, & Komai, 1997;Pirogovsky, Woods, Filoteo, & Gilbert, 2012). Regarding the individual items, only 'tea making' and 'alarm clock' are not related to cognitive dysfunction, further indicating that these items are not cognitively demanding enough to detect early signs of iADL impairment.…”
Section: Reliability and Item-validity Of The Etamsupporting
confidence: 91%
“…We suggest that mild iADL impairment is closely associated with attention deficits. This finding is supported by other studies linking attentional deficits with iADL (Becker et al, 2018;Bronnick et al, 2006). Other cognitive domains did not differ between the PD-MCI patients with a lowered and those with a high ETAM total score.…”
Section: Etam Sensitivity For Iadl Impairment Associated With Pd-mcisupporting
confidence: 88%
See 1 more Smart Citation
“…Among the participants with AD, MCI, and healthy older adults, reduced executive performance has been particularly associated with poorer IADLs, 35,36 and interventions to improve executive functions have been suggested as a means to increase independence. 37 In PD, memory, executive function, processing speed, language, and visuospatial skills have been variably associated with complex IADLs, 10,11,38 although other studies that evaluate performance-based methods of IADL assessment have found no relationship between cognition and functional performance in participants with PD. 3,39 Here, we provide support for associations with both cognitive diagnosis and individual cognitive tests, particularly processing speed and working memory.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the ongoing, longitudinal ABC-PD study [12] is to assess disease progression of PD patients with and without (probable) amyloid beta pathology. One hundred PD patients selected according to their CSF Aß42 profile were recruited from the outpatient clinic of the department of Neurodegeneration at the University of Tübingen.…”
Section: Cohort Bmentioning
confidence: 99%